(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
In Venezuela, manufactured products are of low technological level and added value, thus, there is a need to review the mechanisms that promote the technological development in the country like the funding sources, specifically the venture capital. In this study we analyze the obstacles faced by the venture capital in Venezuela and the government policies to support it. This work is both documentary and field research, which made it possible to collect printed and electronic material on the subject, as well as to survey the related organizations. By analyzing the results, we were able to offer conclusions on the reality of the venture capital in Venezuela, and elaborate recommendations to boost this form of funding as a support mechanism for the technological development.